Evaluasi Pengelolaan Limbah B3 PT Perusahaan Gas Negara TBK – Sales & Operation Regional III (Studi Kasus Offtake Station Waru) - Zakkiyah Salwa Meydhita Nur Sabrina; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2024)
PT Perusahaan Gas Negara Tbk (PGN) - Sales and Operation Region III (SOR III) is a natural gas distribution company. PGN generates hazardous and toxic waste (B3) from operational activities and equipment maintenance. The company manages the waste to reduce the environmental impact through various stages such as reduction, storage, packaging, labelling and transport in collaboration with third parties. The aim of this research is to evaluate the company's B3 waste management practices and, if necessary, propose recommendations for improvement. The research method used was field observation, analysis of internal documents related to B3 waste management and evaluation using the Guttman Scale method. The results of the B3 waste management assessment showed a score of 77.4% and was categorised as "good".